PEMBEBANAN FIDUSIA SECARA FIDUSIA ULANG ATAS SUATU BENDA YANG SAMA SETELAH BERLAKUNYA UNDANG-UNDANG JAMINAN FIDUSIA - Tajuddin Noor Noor (jurnal.unprimdn.ac.id, 2019)
Fiduciary guarantees have been used in Indonesia since the Dutch colonial era as a form of guarantee born from jurisprudence. This form of collateral is widely used in lending and borrowing transactions because the loading process is considered simple, easy, and fast, but does not guarantee legal certainty. Because fiduciary collateral objects are under the authority of the fiduciary giver and are not registered. The issuance of the Fiduciary Guarantee Act No. 42 of 1999 is expected to accommodate the needs of the community regarding the imposition of fiduciary guarantees as a means to assist and provide legal certainty to the parties concerned. The most important part to understand from fiduciary arrangements in this Fiduciary Security Act is about how to regulate fiduciary collateral and whether objects that are subject to fiduciary .